PERSONIFICATION OF GENDER AESTHETICS IN FEMALE IMAGES BY A. P. CHEKHOV, A. I. KUPRIN, I. A. BUNIN (Proceedings of Southern Federal University. Philology, 2026)
10.18522/1995-0640-2026-1-47-55Creating a female image, each artist finds his own details based on his personal sensory experience and worldview. Since beauty is a metaphysical hypostasis that cannot be universally defined, the reception of the ideal female beauty is accompanied by the writer's reflection on the nature of this phenomenon. The analysis of the representation of three female images in the stories of contemporary Russian writers allows us to compare not only the stylistics of their embodiment, but also the philosophical understanding of this phenomenon by each of them. The verbal description of literary characters makes it possible to draw parallels with precedent examples of the world-famous paintings. The linguistic analysis allows us to draw the following conclusions. Chekhov's reception of the female beauty is in grace, natural harmony and chastity, Kuprin's one is in lines and proportions, and Bunin sees it in the dynamics of color, light and fragrance. According to the authors’ speculations It can be concluded that Chekhov here considers the beauty of a woman philosophically, Kuprin – in ontogenesis, and Bunin – in the spirit of pantheism. Key words: female beauty, emotional reaction, portrait features, aesthetic assessment, harmony, grace, verbal painting